Hydrogels for the Application of Articular Cartilage Tissue Engineering: A Review of Hydrogels - Er-Yuan Chuang; Chih-Wei Chiang; Pei-Chun Wong; Chih-Hwa Chen (Advances in Materials Science and Engineering)
The treatment of articular cartilage damage is a major task in the medical science of orthopedics. Hydrogels possess the ability to form multifunctional cartilage grafts since they possess polymeric swellability upon immersion in an aqueous phase. Polymeric hydrogels are capable of physiological swelling and greasing, and they possess the mechanical behavior required for use as articular cartilage substitutes. The chondrogenic phenotype of these materials may be enhanced by embedding living cells. Artificial hydrogels fabricated from biologically derived and synthesized polymeric materials are also used as tissue-engineering scaffolds; with their controlled degradation profiles, the release of stimulatory growth factors can be achieved. In order to make use of these hydrogels, cartilage implants were formulated in the laboratory to demonstrate the bionic mechanical behaviors of physiological cartilage. This paper discusses developments concerning the use of polymeric hydrogels for substituting injured cartilage tissue and assisting tissue growth. These gels are designed with consideration of their polymeric classification, mechanical strength, manner of biodegradation, limitations of the payload, cellular interaction, amount of cells in the 3D hydrogel, sustained release for the model drug, and the different approaches for incorporation into adjacent organs. This article also summarizes the different advantages, disadvantages, and the future prospects of hydrogels.